Perceraian Akibat Beralih Agama (Murtad) Serta Dampak Terhadap Hak Asuh Anak Menurut Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan dan Intruksi Presiden Nomor 1 Tahun 1991 Tentang Kompilasi Hukum Islam - Dwiki Darmansyah (Journal of Law and Islamic Law, 2023)
This paper examines the relationship between the breakup of a marriage that results in the breakup of the relationship as husband and wife. However, with the development of society in problems related to divorce because one of the spouses changes religion, the consequence of divorce punishment, one of which is changing religion, is custody of the child. It was there that a problem arose until now, whether this authority was given to the Religious Courts or the District Courts. Following the Law on the Religious Courts, it is explained that religious courts are designated from that place for people who adhere to the Islamic religion. Based on this explanation, it can be said that the religious court is one of the legitimate Indonesian state courts, with unique judicial characteristics, for every person who is a Muslim in Indonesia. Moreover, custody as a result of divorce from different religions or parents who change religions, legally it is not strictly regulated, so in this matter, it is the judge's consideration in deciding because the point is how to maintain the benefit for those who are not yet mumayyiz, because their primary need is for mother's love. This research method uses normative legal methods, namely library research, meaning that the legal basis is used at the source, namely secondary and primary legal materials. The results of the study show that in the settlement of divorce due to conversion/apostasy in Indonesia, the divorce process due to apostasy is the same as the divorce process in general. The divorce process cannot be separated from the marriage process that the couple used to carry out because a law already regulates this matter. In this regard, the benchmark for hadhanah rights is the benefit for the child, which includes maintaining the child's faith, taking care of the body, developing the child's mental/spiritual and intellectual development, and guaranteeing complete attention or happiness. As for the benefit concerning the child's faith, it must be seen whether he is in a state of concern, namely a situation where he will divert his child's belief.